2018
DOI: 10.12816/0052252
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Ascitic Fluid and Serum Levels of Calprotectin, Procalcitonin and Endocan in Patients With Liver Cirrhosis for Early Diagnosis and Prediction of Spontaneous Bacterial Peritonitis

Abstract: Background: Spontaneous bacterial peritonitis (SBP) is a serious, recurrent, and life-threatening condition developing in cirrhotic patients with a high mortality rate. Its diagnosis is based on ascitic fluid polymorphonuclear leukocytes (PMNs) to be more than 250/? L.Objectives: polymorphonuclear leukocytes (PMNs) to be more than 250/? L. Objective: The aim of the study was to evaluate the ascitic fluid and serum levels of calprotectin, procalcitonin (PCT) and endocan as appropriate markers for predicting and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…When a bacterial strain is isolated in microbiological culture and/or the polymorphonuclear leukocyte count is ≥ 250 in 1 milliliter of ascites fluid (either manually or automatically counted), this is the most sensitive indicator of diagnosis [1]. Nearly all patients with ascites at the time of hospital admission, as well as those who appeared with systemic manifestation of infection as fever, peritoneal infection as generalized dull aching abdominal pain, deterioration of liver condition as hepatic encephalopathy, or rapid deterioration in renal function, are advised to undergo a diagnostic paracentesis [2].…”
Section: Introductionmentioning
confidence: 99%
“…When a bacterial strain is isolated in microbiological culture and/or the polymorphonuclear leukocyte count is ≥ 250 in 1 milliliter of ascites fluid (either manually or automatically counted), this is the most sensitive indicator of diagnosis [1]. Nearly all patients with ascites at the time of hospital admission, as well as those who appeared with systemic manifestation of infection as fever, peritoneal infection as generalized dull aching abdominal pain, deterioration of liver condition as hepatic encephalopathy, or rapid deterioration in renal function, are advised to undergo a diagnostic paracentesis [2].…”
Section: Introductionmentioning
confidence: 99%
“…ng/ml](25) . also, another study found that serum endocan levels were significantly higher in patients with SBP [median (IQ) 3.2 (0.55-5.9)ng/ml] than patients without SBP [median (IQ) 6.2 (5.3-8.75)ng/ml] (26).…”
mentioning
confidence: 99%